Identifikasi Penyebab Penyakit Daun Keriting Kuning pada Tanaman Mentimun - Dwiwiyati Nurul Septariani; Sri Hendrastuti Hidayat; Endang Nurhayati (Jurnal Hama dan Penyakit Tumbuhan Tropika, 2014)
ABSTRACTIdentification of the causal agent of yellow leaf curl disease on cucumbers. Yellow leaf curl disease has been reported to cause serious diseases and yield losses on tobacco, chilli pepper, and tomato plants in Java. Similar symptoms were observed recently on cucumber plants from several growing areas in West Java (Bogor), Central Java (Tegal and Sukoharjo), and Yogyakarta (Sleman). Symptom variations including mosaic, chlorotic spotting, leaf curling, blistering, vein banding, reduction and distortion of leaf and fruit were observed. Serological detection using Enzyme Linked Immunosorbent Assay (ELISA) showed infection of several viruses. Antibodies specific to Squash mosaic comovirus (SqMV), Zucchini yellow mosaic potyvirus (ZyMV), dan Cucumber mosaic cucumovirus (CMV) were reacted positively with field samples. No serological reactions were observed with antibodies to Tobacco ringspot potyvirus (TRSV) and Watermelon mosaic potyvirus (WMV). Molecular detection approach based on Polymerase Chain Reaction was undergone using universal primers for Geminivirus, pAL1v1978 and pAR1c715. DNA fragment 1600 bp in size, was successfully amplified from leaf samples originated from Tegal, Sleman, Bogor, and Sukoharjo. Further identification by nucleotide sequencing indicated that virus isolates causing yellow leaf curl disease on cucumber have highest homology (95.7% to 98.6%) with Tomato leaf curl New Delhi virus-[Cucumber:Indonesia] (AB613825) from Klaten, Central Java, Indonesia.